Critical Literacy-Based Digital Module for Elementary Students - Nurhaedah; Achmad, Widya Karmila Sari (Universitas Pendidikan Ganesha, 2025)
Teaching modules are essential tools that support teachers in delivering material and managing classroom learning activities. However, many modules currently used in elementary schools do not fully meet the required standards. This study aims to validate the development of a digital teaching module based on critical literacy, designed for fifth-grade elementary school students. The validation process involved expert validators as well as a classroom teacher as respondents. Data were collected through validation sheets and structured questionnaires, assessing key aspects such as content relevance, integration of critical literacy, ease of use, student engagement, and technical quality. Data analysis employed descriptive statistics to calculate mean scores and levels of agreement. The findings show that the digital teaching module achieved high average scores across all components, with content relevance and clarity of instructions each scoring 4.0, ease of use 3.9, and integration of critical literacy 3.8. Although student engagement and technical quality received slightly lower scores (3.6 and 3.8, respectively), these values remain within acceptable standards. These results indicate that the digital teaching module is a valid and promising tool for integrating critical literacy into elementary education.